Research on service quality of professional education based on the PZB service quality model - Deng, Xuejun; Liu, Liang; Liu, Xiaojun (Frontiers in Education, 2023)
With the arrival of Internet technology and the information era, China's higher education has entered a new stage of development. In this context, new learning methods represented by "Internet+" have gradually emerged and rapidly spread, and traditional classroom teaching is facing a huge impact. At the same time, more and more students choose to learn independently through online courses due to resource constraints, time and space. This new learning method has posed a great challenge to the traditional education concept. Therefore, how to improve the quality of college education services has become one of the urgent problems to be solved at present. In this paper, from the perspective of service quality of college education, it is of practical significance to apply the theory of hybrid service quality to college hybrid education to explore its service quality improvement strategy. In this paper, the application of the PZB service quality model in professional education teaching is studied and discussed by using the methods of literature, mathematical statistics, and logical analysis. In this paper, the structure of the service quality evaluation system, influencing factors and results analysis, and the summary of improvement suggestions are deeply analyzed.